Legal Problems of Compensation for Breach of Betrothal Agreement - Puangsuwan, Supawich (Rajapark Journal, 2022)
Betrothal is a man and a woman willing to legally get married to each other in the future as stipulated in the Civil and Commercial Code, Article 1435 to Article 1447. The principle is that the man gives or transfers the property, which is an engagement gift, to the woman as evidence that the marriage shall take place, and this will form the betrothal agreement. However, if a party breaches the betrothal agreement or engages in gross misconduct, the other party has the right to terminate the betrothal agreement. The law stipulates that the other party may charge compensation to the default party only in the portion stipulated by law. but it is found that in cases where a man or a woman made payment or became debtor in preparation of the marriage, the supreme court’s judgment does not cover all expenses paid in good faith. However, the law uses the word "good faith," but the scope of which cannot be determined because betrothal is a tradition that is different in each area. It is impossible to use the same principle. Nonetheless, the law gives authority to courts to use their discretion to consider this matter, and courts have given several Supreme Court judgment directions. I have a different opinion from some of your judgments.